2008
DOI: 10.1080/03093640701318672
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing

Abstract: The objective of this study was to compare the effectiveness of irremovable total-contact casts (TCC) and custom-made temporary footwear (CTF) to heal neuropathic foot ulcerations in individuals with diabetes. In this prospective clinical trial, 43 patients with plantar ulcer Grade 1 or 2 (Wagner scale) were randomized to one of two off-loading modalities: TCC or CTF. Outcomes assessed were wound surface area reduction (cm 2 ) and time to wound healing (days) at 2, 4, 8 and 16 weeks. To evaluate safety, possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 13 publications
0
61
0
3
Order By: Relevance
“…34,[51][52][53][54] Conventional or standard therapeutic footwear is not effective in ulcer healing, and the role of custom footwear in this context is not yet clear. 55 Several prospective controlled studies have shown that surgical interventions such as Achilles tendon lengthening, metatarsal-phalangeal joint arthroplasty, and metatarsal head resection may have only limited additional value in ulcer healing compared with conservative treatment. [56][57][58][59][60] Neuroischemic or infected wounds can also be treated with off-loading, although success rates are much lower than for purely neuropathic wounds.…”
Section: The Evidence Base: What Work and What Does Not Work?mentioning
confidence: 99%
“…34,[51][52][53][54] Conventional or standard therapeutic footwear is not effective in ulcer healing, and the role of custom footwear in this context is not yet clear. 55 Several prospective controlled studies have shown that surgical interventions such as Achilles tendon lengthening, metatarsal-phalangeal joint arthroplasty, and metatarsal head resection may have only limited additional value in ulcer healing compared with conservative treatment. [56][57][58][59][60] Neuroischemic or infected wounds can also be treated with off-loading, although success rates are much lower than for purely neuropathic wounds.…”
Section: The Evidence Base: What Work and What Does Not Work?mentioning
confidence: 99%
“…A systematic review and meta‐analysis, including ten randomized and non‐randomized clinical studies and a cumulative total of 524 patients , showed significantly better healing for non‐removable offloading compared with removable offloading (RR 1.43; 95% CI 1.11–1.84, p = 0.001) . However, stratified by type of removable device, five RCTs found a trend but no statistically significant difference between non‐removable knee‐high offloading devices and removable knee‐high walkers (RR = 1.23, 95% CI 0.96–1.58, p = 0.085) .…”
Section: Casting and Prefabricated Healing Devicesmentioning
confidence: 99%
“…The use of custom‐made temporary shoes for healing relatively large and deep ulcers, some with mild infection, in neuropathic patients of which many had moderate PAD, was examined in one RCT at low risk of bias. The study found relatively low healing proportions, and equivalence in healing proportion and reduction in ulcer area between the temporary shoes and a TCC . Based on the limited number of controlled studies, the quality of evidence is low.…”
Section: Casting and Prefabricated Healing Devicesmentioning
confidence: 99%
“…Si une plaie ou les pathologies intriquées impliquent de supprimer tout appui, le choix des solutions est restreint ; pour notre part, nous utilisons chaque fois que possible les bottes à appui sous-rotulien, notamment dans le cas de pied de Charcot. Par contre, si la décharge doit être localisée, des expériences alimentent la recherche de solutions alternatives à la contention plâtrée [9,10]. Un contrôle des pressions locales poursuit un double objectif pour juger des solutions adoptées : quelle est la réalité de la décharge sur la zone ?…”
Section: Nécessité De La Déchargeunclassified
“…La contribution de la baropodométrie à l'éducation du patient pour lutter contre les effets pervers des solutions thérapeutiques amovibles passe par son intégration dans un projet éducatif global. C'est un enjeu important [9], car la question de la compliance [10] reste débattue et pourrait dépendre des moyens d'information et de la tactique d'accompagnement de la prise en charge du patient de ses aidants. Au poids des mots, nous cherchons à ajouter le choc des photos.…”
Section: Limites Et Intérêt De La Baropodométrie Par Plate-formeunclassified